217 The impact of anti-bullying policies at the school level: a mixed-method analysis of implementation practices. (5th May 2020) - Nam, Yoon-Sung; Calvert, Collin; McFalls, Matt; Hernandez, Ashley; Adkins, Sarah; Ramirez, Marizen
Abstract : Statement of Purpose: All 50 states have adopted anti-bullying legislation in an effort to reduce bullying in schools. However, little research has been conducted to understand how schools implement their anti-bullying policies. This study illustrates how Maine schools implemented their district's anti-bullying policies and presents facilitators and challenges to implementing these policies. Methods/Approach: Semi-structured interviews and surveys were administered to twenty-two school personnel involved in the implementing anti-bullying policies (administrators, counselors, teachers, and support staff) across six schools in the state of Maine. Respondents were asked to recount how bullying allegations are reported, their experience investigating bullying allegations, how safety measures and responses plans are implemented, and discuss the content of the anti-bullying training provided. Results: Respondents identified many challenges to implementing the policy that included limited time and resources to investigate bullying allegations. Contextual challenges to reporting bullying allegations also emerged (e.g., fear of retaliation). One major challenge that emerged across all interviews was related to investigating cyberbullying allegations. Rural schools overall indicated it was easier to implement the anti-bullying policy when compared to urban schools. Conclusions: Interview findings have shown that implementation of anti-bullying policies is a complex process that involves substantial effort and time for schools to carry out Maine's required policy guidelines. School staff acknowledged that the ability and time to complete the investigation procedure determined how the school responded to bullying allegations. Significance and Contributions to Injury and Violence Prevention Science: Bullying behavior now includes social/relational interactions, gender identity, sexual expression, race/ethnicity, and body image, ongoing education of the various forms of bullying is a necessary step to address bullying. Therefore, future research should explore how training educates school personnel on the different forms of bullying and how training can improve their competencies to identify and address bullying incidences when and after it occurs.